2015
DOI: 10.1038/cddiscovery.2015.26
|View full text |Cite
|
Sign up to set email alerts
|

The MDM2 small-molecule inhibitor RG7388 leads to potent tumor inhibition in p53 wild-type neuroblastoma

Abstract: Neuroblastoma is an aggressive pediatric malignancy which is >98% p53 wild-type at diagnosis. As a primary repressor of p53 activity and part of a p53-activated negative feedback loop, targeting of mouse double minute 2 homolog (MDM2) is an attractive therapeutic approach to reactivation of p53. Since development of the first selective MDM2 inhibitor, Nutlin-3a, newer compounds have been developed for increased potency and improved bioavailability. Herein, we sought to determine the efficacy and specificity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
40
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 33 publications
(55 reference statements)
9
40
0
Order By: Relevance
“…The PD profile was consistent with the PK profile, mechanism of action, and previous studies. 11,25,27,32 The analysis of PD biomarkers of response to RO6839921 alone showed changes in MIC-1, p21, p53 and Ki67, consistent with our previous in vitro observations of idasanutlin mediated anti-tumour activity. 10 Our study is the only preclinical study of idasanutlin in neuroblastoma so far to include MIC-1 as a PD biomarker, and demonstrated that in response to combination treatment MIC-1 was the most responsive biomarker in the SHSY5Y-Luc model and p21 in the NB1691-Luc model.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The PD profile was consistent with the PK profile, mechanism of action, and previous studies. 11,25,27,32 The analysis of PD biomarkers of response to RO6839921 alone showed changes in MIC-1, p21, p53 and Ki67, consistent with our previous in vitro observations of idasanutlin mediated anti-tumour activity. 10 Our study is the only preclinical study of idasanutlin in neuroblastoma so far to include MIC-1 as a PD biomarker, and demonstrated that in response to combination treatment MIC-1 was the most responsive biomarker in the SHSY5Y-Luc model and p21 in the NB1691-Luc model.…”
Section: Discussionsupporting
confidence: 90%
“…5 TP53 mutations are rare in neuroblastoma even at relapse, however upstream p53 pathway inactivation through MDM2 amplification (2.5-7%) and p14 ARF abnormalities (2-22% homozygous deletion; 7% methylation), have been reported particularly at relapse and support the use of MDM2 antagonists. [6][7][8][9] We and others have demonstrated highly potent anti-tumour effects of idasanutlin in preclinical neuroblastoma models, alone and in combination with chemotherapy currently used in the treatment of high-risk neuroblastoma, namely cisplatin, doxorubicin, topotecan (induction), busulfan (consolidation) and temozolomide (relapse), 10,11 and recently combinations with other targeted agents have been reported. 12,13 In addition, another MDM2 antagonist in clinical trials, MI-773 (SAR405838), has been shown to enhance doxorubicin mediated cytotoxicity in neuroblastoma cell lines.…”
Section: Introductionmentioning
confidence: 99%
“…39 Zhou et al 10 reported that MDM2-overexpressed/ TP53 -null cancer cells are associated with increased VEGF mRNA expression compared with MDM2-negative/ TP53 -null cells. Furthermore, Lakoma et al 11 showed that pharmacologic inhibition of MDM2 is associated with a decrease in hypoxia-inducible factor 1α and VEGF expression in cancer cell lines. TP53 alterations also have been reported to be associated with increased VEGF expression in preclinical models as well as in patients with lung adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…10 In addition, suppression of MDM2 activity with a small-molecule inhibitor leads to decreased hypoxia-inducible factor 1α and VEGF expression, which support a role for MDM2 in angiogenesis. 11 TP5 3 mutations also lead to increased VEGF-A expression 12,13 and have been associated with increased responsiveness to VEGF/ VEGF receptor inhibitor therapy. 1416 Taken together, these data suggest that MDM2 promotes angiogenesis through either inhibition of p53 or mechanisms independent of p53.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to preclinical assessment of RG7338 as therapy for neuroblastoma (L. Chen et al, 2015; Lakoma et al, 2015), childhood sarcoma (Phelps et al, 2015), and ovarian carcinoma(Zanjirband, Edmondson, & Lunec, 2016), RG7338 is involved in five other phase I/II studies currently recruiting participants: in combination with obinutuzumab, a novel anti-CD20 mAB, for relapsed or refractory follicular lymphoma or diffuse large B-cell lymphoma (Illidge et al, 2015) (NCT02624986), in combination with Venetoclax, a novel BH3-mimetic/Bcl-2 inhibitor, for patients over 60 with relapsed or refractory AML who are ineligible for cytotoxic therapy (Woyach & Johnson, 2015) (NCT02670044), in combination with dexamethasone and ixazomib citrate, a novel proteasome inhibitor, for refractory multiple myeloma (P. G. Richardson et al, 2015) (NCT02633059), as a standalone drug for polycythemia vera and essential thrombocythemia (NCT02407080), and in a study designed to compare oral vs intravenous administration of RG7388 in terms of excretion balance, pharmacokinetics, metabolism, and bioavailability in patients with solid tumors (NCT02828930).…”
Section: Small Molecule Wild-type P53 Activatorsmentioning
confidence: 99%